Pengaruh Metode POE2WE Dalam Kemampuan Menulis Deskirpsi Mahasiswa Universitas Indraprasta PGRI - haryanti, ade siti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to determine the effect of the POE2WE method in learning to write description. The research method used is a quantitative descriptive research method. The results of the study are that there is a significant effect of apllying the POE2WE method to the ability to write descriptions, this can be seen from tcount ≥ ttable or 5,99 ≥2,00 so it can be concluded that there is an effect of applying the POE2WE method to the ability to write descriptions of PBSI students at Indraprasta PGRI University.